Hybrid 2D/3D g-C3N4/BiVO4 photocatalyst decorated with RGO for boosted photoelectrocatalytic hydrogen production from natural lake water and photocatalytic degradation of antibiotics - Samsudin, M.F.R. (Elsevier B.V., 2020)
The photocharge carrier separation and migration within the heterostructure interface plays a pivotal role in the photoelectrocatalytic hydrogen production and the photocatalytic degradation activity. Herein, a series of the 2D/3D g-C3N4/BiVO4 photocatalyst decorated with RGO were successfully fabricated via a modified doctor blading technique. The as-developed 2D/3D RGO@ g-C3N4/BiVO4 photocatalysts were further evaluated for its bifunctional applications in photoelectrocatalytic hydrogen production and photocatalytic degradation of antibiotics (amoxicillin and ciprofloxacin). The optimized 1.2 wt RGO@g-C3N4/BiVO4 photocatalyst demonstrated the maximum photoelectrocatalytic hydrogen production of 63.5 mmol/h with a photocurrent density of 14.44 mA/cm2 (ABPE of 0.41 at â0.05 V vs. Ag/AgCl). Concomitantly, the optimized as-developed photocatalysts were capable of degrading 91.9 and 84.3 amoxicillin and ciprofloxacin, respectively under visible-light illumination. The comprehensive kinetics and isotherms analysis revealed that the 1.2 wt RGO@g-C3N4/BiVO4 photocatalyst obeyed the pseudo-first-order and Temkin models. In addition, the as-developed optimized photocatalyst was found to remain stable even after three cyclic activity with no obvious change in both photoelectrocatalytic and photocatalytic performance. This can be attributed to the synergistic interaction between RGO with the 2D/3D g-C3N4/BiVO4 photocatalyst which promotes robust interfacial contact at the heterostructure interface and allows smooth photocharge carrier transfer, results in limited recombination of the photocharge carriers. Finally, details of the photoelectrocatalytic and photocatalytic mechanisms were revealed along with the ciprofloxacin and amoxicillin degradation pathways. Â© 2020 Elsevier B.V.